2016
DOI: 10.3892/mmr.2016.5488
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of circulating adrenomedullin following treatment with TU-100 in patients with Crohn's disease

Abstract: Daikenchuto (TU‑100) is a traditional Japanese medicine that is widely used to treat intestinal symptoms. The mechanisms underlying it effects on the circulating levels of adrenomedullin (ADM) are of interest. In addition, the effect of TU‑100 in the treatment of Crohn's disease (CD) in humans remains to be elucidated. The primary objective of the present study was to evaluate the effect of TU‑100 on the circulating ADM levels in patients with active CD. An additional objective was to assess the effect of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Furthermore, in a clinical study, continuous intravenous infusion of hAM ameliorated the symptoms of intractable UC without adverse side effects [Ashizuka et al ]. Moreover, a traditional Japanese medicine (Daikenchuto) increases circulating hAM levels and aids in healing Crohn's disease [Kominato et al, ]. As we described above, the anti‐inflammatory properties of hAM make it an effective candidate therapeutic agent for the treatment of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a clinical study, continuous intravenous infusion of hAM ameliorated the symptoms of intractable UC without adverse side effects [Ashizuka et al ]. Moreover, a traditional Japanese medicine (Daikenchuto) increases circulating hAM levels and aids in healing Crohn's disease [Kominato et al, ]. As we described above, the anti‐inflammatory properties of hAM make it an effective candidate therapeutic agent for the treatment of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…ADM has various bioactivation functions, including a hypotensive effect by vasodilation and roles in cell migration, differential regulation, anti-inflammation, and increasing vascular flow. Research using rodents revealed that ADM is induced by TJ-100 administration, and that TJ-100 has many effects, e.g., accelerating gastrointestinal transit and increasing intestinal blood flow, and an anti-inflammation effect [ 17 ]. The concentration of ADM in human blood plasma has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Daikenchuto (TJ-100) is a traditional herbal medicine, also called Kampo, composed of Capsicum Annuum , dried ginger, ginseng and cerealose (Endo et al, 2017 ) and can be used for gastrointestinal diseases including intestinal obstruction and Crohn's disease (Kominato et al, 2016 ; Okada et al, 2016 ). Some studies found that TJ-100 can suppress tumor development and alleviate side effects of surgery (Yoshikawa et al, 2015 ; Nagata et al, 2016 ; Hasebe and Matsukawa, 2017 ).…”
Section: Chinese Herbal Formulations For Dsmmentioning
confidence: 99%